CHILDREN AT RISK: SOCIAL POLICIES AND SERVICES AND THEIR IMPACT IN ALBANIA - Kulluri, Eliona Bimbashi; Allmuça, Marsela (Ревија за социјална политика/Journal of Social Policy, 2015)
Albania society has experienced a prolonged transition which isaccompanied with substantial changes that have caused effects on familiesand especially children’s lives. Groups of children at risk of socialexclusion in Albania are: working and street children, children in conflictwith law, poor children, Roma children, children who are subjected toviolence and trafficking, children involved in the phenomenon of theblood feud, children with disabilities and children living in rural areas.This categories shares very difficult experiences such as living inminimal conditions, suffer lack of access to key services such as lack ofhealth services, very low attendance and lack of access to educationalinstitutions. These consequences associate with lack or inadequacy ofappropriate service provision and lack of coordination between theresponsible structures.The purpose of this study is to analyze the situation of children atrisk in Albania, policies and services for this category, their impact aswell. For the realization of the study are used methods of secondary dataanalysis combined with qualitative data provided through semi-structuredinterviews with key persons in different decision-making level, and focusgroups with children at risk.Key findings are related with lack of policies to address theprevention, protection, assisted voluntary return, repatriation andreintegration of trafficked children; gaps in the implementation of theNational Action Plan to Combat Trafficking in Children; lack ofcoordination between institutions and services; services and programs atcentral and local level for children as Children Protection Units are notspread across all the territory; there is a reduction in the number ofresidential and day services and increase of community once, etc.Research findings conclude with the need for improved social carelegislation and creating of suitable legal acts, which emphasizes the role ofstakeholders in supporting children; Foreseen policies that address theprevention, protection, assisted voluntary return, repatriation andreintegration of trafficked children; to include the elimination of childlabour in general policies and national programs; creating multi-sectoralmechanisms to identify victims of trafficking, especially traffickedchildren, etc.
Keywords: children at risk; needs; social services; social care; social policies